Sintesa dan Karakteristik Karbon Aktif dari Batang Pisang Kepok (Musa acuminata) Sebagai Adsorben pada Penjernihan Minyak Goreng Bekas - Primastiyaningayu, Andini; Rismala, Erika Indri; Triana, Nurul Widji (Jurnal Ilmiah Teknik Kimia, 2024)
Kepok banana stems have a cellulose content of 58.6466%. The cellulose content means that Kepok banana stems can be used as a basic ingredient for making active carbon. Activated carbon is a material that has high porosity and can be used for absorption which can remove impurities liquid or gas. Process for making activated carbon is cutting banana stems into small pieces and washed, then drying with sun during 7 days. After that, carbonized at 300℃ for 1 hour. Carbonizasition product were ground and sieved with a 100 mesh sieve and activated with NaOH 0.5; 0.75; 1; 1.25 and 1.5 N for 12; 18; 24; 30; and 36 hours. Then, drying in oven at temperature of 100℃ until constant weight. The best activated carbon is activator concentration of 1.5 N NaOH for 12 hours with a water content of 7.8496%, ash content of 9.7186%, and bound carbon content of 65.3479%. SEM test results of activated carbon from banana stems before application have a porous morphological structure and after application the active carbon pores are seen to be closed. Percentage reduction FFA reach 94.8057% and the reduction peroxide reach 86.8978%.